5.2.44 Problems 4301 to 4400

Table 5.255: Second order linear ODE

#

ODE

Mathematica

Maple

15379

\[ {}x^{2} y^{\prime \prime }-5 x y^{\prime }+8 y = 0 \]

15380

\[ {}x^{2} y^{\prime \prime }-2 y = 0 \]

15381

\[ {}x^{2} y^{\prime \prime }-2 x y^{\prime } = 0 \]

15382

\[ {}2 x^{2} y^{\prime \prime }-x y^{\prime }+y = 0 \]

15383

\[ {}x^{2} y^{\prime \prime }-5 x y^{\prime }+9 y = 0 \]

15384

\[ {}x^{2} y^{\prime \prime }+5 x y^{\prime }+4 y = 0 \]

15385

\[ {}4 x^{2} y^{\prime \prime }+y = 0 \]

15386

\[ {}x^{2} y^{\prime \prime }-19 x y^{\prime }+100 y = 0 \]

15387

\[ {}x^{2} y^{\prime \prime }-5 x y^{\prime }+29 y = 0 \]

15388

\[ {}x^{2} y^{\prime \prime }-x y^{\prime }+10 y = 0 \]

15389

\[ {}x^{2} y^{\prime \prime }+5 x y^{\prime }+29 y = 0 \]

15390

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }+y = 0 \]

15391

\[ {}2 x^{2} y^{\prime \prime }+5 x y^{\prime }+y = 0 \]

15392

\[ {}4 x^{2} y^{\prime \prime }+37 y = 0 \]

15393

\[ {}x^{2} y^{\prime \prime }+x y^{\prime } = 0 \]

15394

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }-25 y = 0 \]

15395

\[ {}4 x^{2} y^{\prime \prime }+8 x y^{\prime }+5 y = 0 \]

15396

\[ {}3 x^{2} y^{\prime \prime }-7 x y^{\prime }+3 y = 0 \]

15397

\[ {}x^{2} y^{\prime \prime }-2 x y^{\prime }-10 y = 0 \]

15398

\[ {}4 x^{2} y^{\prime \prime }+4 x y^{\prime }-y = 0 \]

15399

\[ {}x^{2} y^{\prime \prime }-11 x y^{\prime }+36 y = 0 \]

15400

\[ {}x^{2} y^{\prime \prime }-x y^{\prime }+y = 0 \]

15401

\[ {}x^{2} y^{\prime \prime }-x y^{\prime }+2 y = 0 \]

15402

\[ {}x^{2} y^{\prime \prime }-3 x y^{\prime }+13 y = 0 \]

15411

\[ {}y^{\prime \prime }+4 y = 24 \,{\mathrm e}^{2 x} \]

15412

\[ {}y^{\prime \prime }+4 y = 24 \,{\mathrm e}^{2 x} \]

15413

\[ {}y^{\prime \prime }+2 y^{\prime }-8 y = 8 x^{2}-3 \]

15414

\[ {}y^{\prime \prime }+2 y^{\prime }-8 y = 8 x^{2}-3 \]

15415

\[ {}y^{\prime \prime }-9 y = 36 \]

15416

\[ {}y^{\prime \prime }-3 y^{\prime }-10 y = -6 \,{\mathrm e}^{4 x} \]

15417

\[ {}y^{\prime \prime }-3 y^{\prime }-10 y = 7 \,{\mathrm e}^{5 x} \]

15418

\[ {}y^{\prime \prime }+6 y^{\prime }+9 y = 169 \sin \left (2 x \right ) \]

15419

\[ {}x^{2} y^{\prime \prime }-4 x y^{\prime }+6 y = 10 x +12 \]

15421

\[ {}y^{\prime \prime }-3 y^{\prime }-10 y = {\mathrm e}^{4 x} \]

15422

\[ {}y^{\prime \prime }-3 y^{\prime }-10 y = {\mathrm e}^{5 x} \]

15423

\[ {}y^{\prime \prime }-3 y^{\prime }-10 y = -18 \,{\mathrm e}^{4 x}+14 \,{\mathrm e}^{5 x} \]

15424

\[ {}y^{\prime \prime }-3 y^{\prime }-10 y = 35 \,{\mathrm e}^{5 x}+12 \,{\mathrm e}^{4 x} \]

15425

\[ {}x^{2} y^{\prime \prime }-4 x y^{\prime }+6 y = 1 \]

15426

\[ {}x^{2} y^{\prime \prime }-4 x y^{\prime }+6 y = x \]

15427

\[ {}x^{2} y^{\prime \prime }-4 x y^{\prime }+6 y = 22 x +24 \]

15428

\[ {}x^{2} y^{\prime \prime }-7 x y^{\prime }+15 y = x^{2} \]

15429

\[ {}x^{2} y^{\prime \prime }-7 x y^{\prime }+15 y = x \]

15430

\[ {}x^{2} y^{\prime \prime }-7 x y^{\prime }+15 y = 1 \]

15431

\[ {}x^{2} y^{\prime \prime }-7 x y^{\prime }+15 y = 4 x^{2}+2 x +3 \]

15432

\[ {}y^{\prime \prime }+9 y = 52 \,{\mathrm e}^{2 x} \]

15433

\[ {}y^{\prime \prime }-6 y^{\prime }+9 y = 27 \,{\mathrm e}^{6 x} \]

15434

\[ {}y^{\prime \prime }+4 y^{\prime }-5 y = 30 \,{\mathrm e}^{-4 x} \]

15435

\[ {}y^{\prime \prime }+3 y^{\prime } = {\mathrm e}^{\frac {x}{2}} \]

15436

\[ {}y^{\prime \prime }-3 y^{\prime }-10 y = -5 \,{\mathrm e}^{3 x} \]

15437

\[ {}y^{\prime \prime }+9 y = 10 \cos \left (2 x \right )+15 \sin \left (2 x \right ) \]

15438

\[ {}y^{\prime \prime }-6 y^{\prime }+9 y = 25 \sin \left (6 x \right ) \]

15439

\[ {}y^{\prime \prime }+3 y^{\prime } = 26 \cos \left (\frac {x}{3}\right )-12 \sin \left (\frac {x}{3}\right ) \]

15440

\[ {}y^{\prime \prime }+4 y^{\prime }-5 y = \cos \left (x \right ) \]

15441

\[ {}y^{\prime \prime }-3 y^{\prime }-10 y = -4 \cos \left (x \right )+7 \sin \left (x \right ) \]

15442

\[ {}y^{\prime \prime }-3 y^{\prime }-10 y = -200 \]

15443

\[ {}y^{\prime \prime }+4 y^{\prime }-5 y = x^{3} \]

15444

\[ {}y^{\prime \prime }-6 y^{\prime }+9 y = 18 x^{2}+3 x +4 \]

15445

\[ {}y^{\prime \prime }+9 y = 9 x^{4}-9 \]

15446

\[ {}y^{\prime \prime }+9 y = x^{3} \]

15447

\[ {}y^{\prime \prime }+9 y = 25 x \cos \left (2 x \right ) \]

15448

\[ {}y^{\prime \prime }-6 y^{\prime }+9 y = \sin \left (x \right ) {\mathrm e}^{2 x} \]

15449

\[ {}y^{\prime \prime }+9 y = 54 x^{2} {\mathrm e}^{3 x} \]

15450

\[ {}y^{\prime \prime } = 6 x \,{\mathrm e}^{x} \sin \left (x \right ) \]

15451

\[ {}y^{\prime \prime }-2 y^{\prime }+y = \left (-6 x -8\right ) \cos \left (2 x \right )+\left (8 x -11\right ) \sin \left (2 x \right ) \]

15452

\[ {}y^{\prime \prime }-2 y^{\prime }+y = \left (12 x -4\right ) {\mathrm e}^{-5 x} \]

15453

\[ {}y^{\prime \prime }+9 y = 39 \,{\mathrm e}^{2 x} x \]

15454

\[ {}y^{\prime \prime }-3 y^{\prime }-10 y = -3 \,{\mathrm e}^{-2 x} \]

15455

\[ {}y^{\prime \prime }+4 y^{\prime } = 20 \]

15456

\[ {}y^{\prime \prime }+4 y^{\prime } = x^{2} \]

15457

\[ {}y^{\prime \prime }+9 y = 3 \sin \left (3 x \right ) \]

15458

\[ {}y^{\prime \prime }-6 y^{\prime }+9 y = 10 \,{\mathrm e}^{3 x} \]

15459

\[ {}y^{\prime \prime }-3 y^{\prime }-10 y = \left (72 x^{2}-1\right ) {\mathrm e}^{2 x} \]

15460

\[ {}y^{\prime \prime }-3 y^{\prime }-10 y = 4 x \,{\mathrm e}^{6 x} \]

15461

\[ {}y^{\prime \prime }-10 y^{\prime }+25 y = 6 \,{\mathrm e}^{5 x} \]

15462

\[ {}y^{\prime \prime }-10 y^{\prime }+25 y = 6 \,{\mathrm e}^{-5 x} \]

15463

\[ {}y^{\prime \prime }+4 y^{\prime }+5 y = 24 \sin \left (3 x \right ) \]

15464

\[ {}y^{\prime \prime }+4 y^{\prime }+5 y = 8 \,{\mathrm e}^{-3 x} \]

15465

\[ {}y^{\prime \prime }-4 y^{\prime }+5 y = \sin \left (x \right ) {\mathrm e}^{2 x} \]

15466

\[ {}y^{\prime \prime }-4 y^{\prime }+5 y = \sin \left (x \right ) {\mathrm e}^{-x} \]

15467

\[ {}y^{\prime \prime }-4 y^{\prime }+5 y = 100 \]

15468

\[ {}y^{\prime \prime }-4 y^{\prime }+5 y = {\mathrm e}^{-x} \]

15469

\[ {}y^{\prime \prime }-4 y^{\prime }+5 y = 10 x^{2}+4 x +8 \]

15470

\[ {}y^{\prime \prime }+9 y = \sin \left (x \right ) {\mathrm e}^{2 x} \]

15471

\[ {}y^{\prime \prime }+y = 6 \cos \left (x \right )-3 \sin \left (x \right ) \]

15472

\[ {}y^{\prime \prime }+y = 6 \cos \left (2 x \right )-3 \sin \left (2 x \right ) \]

15473

\[ {}y^{\prime \prime }-4 y^{\prime }+5 y = x^{3} {\mathrm e}^{-x} \sin \left (x \right ) \]

15474

\[ {}y^{\prime \prime }-4 y^{\prime }+5 y = x^{3} {\mathrm e}^{2 x} \sin \left (x \right ) \]

15475

\[ {}y^{\prime \prime }-5 y^{\prime }+6 y = x^{2} {\mathrm e}^{-7 x}+2 \,{\mathrm e}^{-7 x} \]

15476

\[ {}y^{\prime \prime }-5 y^{\prime }+6 y = x^{2} \]

15477

\[ {}y^{\prime \prime }-5 y^{\prime }+6 y = 4 \,{\mathrm e}^{-8 x} \]

15478

\[ {}y^{\prime \prime }-5 y^{\prime }+6 y = 4 \,{\mathrm e}^{3 x} \]

15479

\[ {}y^{\prime \prime }-5 y^{\prime }+6 y = x^{2} {\mathrm e}^{3 x} \]

15480

\[ {}y^{\prime \prime }-5 y^{\prime }+6 y = \cos \left (2 x \right ) x^{2} \]

15481

\[ {}y^{\prime \prime }-5 y^{\prime }+6 y = x^{2} {\mathrm e}^{3 x} \sin \left (2 x \right ) \]

15482

\[ {}y^{\prime \prime }-4 y^{\prime }+20 y = {\mathrm e}^{4 x} \sin \left (2 x \right ) \]

15483

\[ {}y^{\prime \prime }-4 y^{\prime }+20 y = {\mathrm e}^{2 x} \sin \left (4 x \right ) \]

15484

\[ {}y^{\prime \prime }-4 y^{\prime }+20 y = x^{3} \sin \left (4 x \right ) \]

15485

\[ {}y^{\prime \prime }-10 y^{\prime }+25 y = 3 x^{2} {\mathrm e}^{5 x} \]

15486

\[ {}y^{\prime \prime }-10 y^{\prime }+25 y = 3 x^{4} \]

15501

\[ {}y^{\prime \prime }-6 y^{\prime }+9 y = 27 \,{\mathrm e}^{6 x}+25 \sin \left (6 x \right ) \]